My husbang Puyi The last emperor of China - Li Shuxian; Wang Qingxiang; Ni Na (Beijing China Intercontinental Press, 2017)
This book is recalled by the widow Li Shuxian of the Last Emperor Pu Yi and written by Wang Qingxiang, the research specialist of Pu Yi. With more than 100 pictures reflecting the family life and work of Pu Yi, this book is a true representation of Pu Yi's second half of life as a socialist citizen, including his marriage, family life, daily work, experience in the 'Cultural Revolution' as well as the real situation of his dying of renal cancer.
Preface -- My childhood -- Seeing Puyi for the first time -- My courtship with the last emperor of China -- The setting of our love -- The last emperor's grand nuptials -- The first week of our honeymoon -- Hopes of having children vanish into thin air -- Teaching Puyi domestic chores and how to live a normal life -- Hangovers from the previous lifestyle of the royal family -- Mortals and secularity - Puyi - a great fan of Peking Opera -- Accompanying my husband back to the place where he ascended the throne as emperor -- Visiting historical and cultural sites together with Puyi -- Our sincere love -- The refusing of the feudal protocols -- Reunion with the former servants -- Puyi's contacts with people from all circles of society -- Receiving foreign guests with Puyi -- The publishing of the "Earth Shattering" book -- The tour to Southeast China -- The tour to Northwest China -- Being attacked by cancer -- "Tricky" situation that happened in Puyi's ward -- Friendship with our neighbour -- Performing the rights of a citizen -- "Hurricane" blew suddenly -- The Puyi who dared to speak out the truth -- Our venture in "Red August" -- Bitter taste of revenge -- Being in bondage to an incurable disease -- Puyi's last summer -- I watched Puyi passing away -- Puyi's memorial ceremony was held thirteen years later -- Publishing of my memoir and the "Puyi Craze" -- The publishing of the second half of Puyi's life -- Apologies from Edward Behr -- Drawing a satisfactory conclusion to the history -- Epilogue
Keywords: Puyi -- 1906-1967.; Kings and rulers